2002
DOI: 10.1002/jbm.a.10423
|View full text |Cite
|
Sign up to set email alerts
|

Surface‐dependent conformations of human plasma fibronectin adsorbed to silica, mica, and hydrophobic surfaces, studied with use of Atomic Force Microscopy

Abstract: Human plasma fibronectin (Fn) is a large flexible protein stabilized by intermolecular ionic interactions forming a compact structure. On altering solution conditions, the structure can revert to a more expanded state, thereby exposing previously hidden domains (e.g., cell-binding sites). Electron microscopy images of Fn air-sprayed onto mica surfaces show elongated protein structures, indicating a surface-induced structural change. This makes it interesting to investigate the influence of surface properties o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

19
256
1
2

Year Published

2006
2006
2021
2021

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 210 publications
(278 citation statements)
references
References 44 publications
19
256
1
2
Order By: Relevance
“…Under physiological conditions, FN adheres more strongly in its compact conformation on hydrophobic surfaces 39 , which may also cause subsequent denaturation of the FN secondary structure to increase substrate binding affinity 40 . The compact conformation of FN is stabilized by intermolecular bonds 41 but can be disrupted by interacting surface groups, particularly hydrophilic and negatively charged surfaces, causing the protein to adopt a more unfolded conformation 25,42 . In this conformation, the protein can interact via different domain regions that are specific to various ECM proteins (e.g.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Under physiological conditions, FN adheres more strongly in its compact conformation on hydrophobic surfaces 39 , which may also cause subsequent denaturation of the FN secondary structure to increase substrate binding affinity 40 . The compact conformation of FN is stabilized by intermolecular bonds 41 but can be disrupted by interacting surface groups, particularly hydrophilic and negatively charged surfaces, causing the protein to adopt a more unfolded conformation 25,42 . In this conformation, the protein can interact via different domain regions that are specific to various ECM proteins (e.g.…”
Section: Resultsmentioning
confidence: 99%
“…By using Atomic Force Microscopy (AFM), the interaction of proteins can be directly probed at the single molecule level to give insight into biophysical processes such as binding kinetics 23 and force-induced conformations 24 . Single molecule studies take into account the multiplicity of protein interactions, especially in the case of large, modular FN protein that can exist in compact, semi-compact and extended conformations 25 , as well as having polyampholyte characteristics that makes it easily deformable on high charge density surfaces 26 . Furthermore, the complex surface properties of conducting polymers, due to different oxidation states 27 , inhomogenous 44 doping 28 and phase separation of properties (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Subsequent membrane attachment, membrane spread, and cellular growth are controlled by internal cellular cues initiated by integrins, and it has been demonstrated that the response is heavily mediated by the surface wet-ability and surface charge (Kim et al, 2001;Rouhi, 1999). Hydrophilic and charged surfaces allow fibronectin (Fn), an extracellular protein which allows cell membrane to surface binding, to unravel and elongate as it is absorbed onto the surface, whereas hydrophobic surfaces show Fn is absorbed in its natural, compact, and rounded form (Bergkvist et al, 2003). Cells show little reactivity with Fn in solution, so elongation is one important factor for cell membrane reactions to occur (Bergkvist et al, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…When adsorbed onto biomaterials, Fn undergoes a conformational change from a globular structure to extended structure, depending on surface properties such as surface charge, hydrophobicity, hydrophilicity, and plays a critical role in mediating cell responses. To determine the role of Fn in mediating cell responses, adsorption of Fn both in molecularly isolated and aggregated states has been extensively investigated on various kinds of substrates, such as silica [26], methylated silica [26], mica [26,28] titanium [27], poly(metylmetacrylate) [28], sulfonated polystyrene [29], and glass [30] by using AFM, scanning electron microscopy (SEM), and fluorescence resonance energy transfer. Although adsorption of Fn is thus well-documented, little is known about the effect of substratum surface nano-and micro-pattern roughness on such adsorption [31].…”
Section: Introductionmentioning
confidence: 99%